2020
DOI: 10.1073/pnas.1916452117
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of oligomer and amyloid fibril formation by yeast prion Sup35 observed by high-speed atomic force microscopy

Abstract: The yeast prion protein Sup35, which contains intrinsically disordered regions, forms amyloid fibrils responsible for a prion phenotype [PSI+]. Using high-speed atomic force microscopy (HS-AFM), we directly visualized the prion determinant domain (Sup35NM) and the formation of its oligomers and fibrils at subsecond and submolecular resolutions. Monomers with freely moving tail-like regions initially appeared in the images, and subsequently oligomers with distinct sizes of ∼1.7 and 3 to 4 nm progressively accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
3
23
1
Order By: Relevance
“…only observed in ~ 2 consecutive frames before leaving the scan area, and show an indistinct morphology likely owing to artefact when tracking fast moving objects [8]. Recently, HS-AFM imaging at 0.05 sec intervals of fast diffusing yeast prion Sup35 NM monomers show similar difficulty in delineating an accurate morphology [9]. Eventually the prion Sup35 NM monomers become 'invisible' at slower imaging intervals of > 0.2 secs.…”
Section: Ex-situ Method: Effect Of Ph On Aβ Peptide Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…only observed in ~ 2 consecutive frames before leaving the scan area, and show an indistinct morphology likely owing to artefact when tracking fast moving objects [8]. Recently, HS-AFM imaging at 0.05 sec intervals of fast diffusing yeast prion Sup35 NM monomers show similar difficulty in delineating an accurate morphology [9]. Eventually the prion Sup35 NM monomers become 'invisible' at slower imaging intervals of > 0.2 secs.…”
Section: Ex-situ Method: Effect Of Ph On Aβ Peptide Solutionsmentioning
confidence: 99%
“…One such single molecule technique, High-Speed Atomic Fore Microscopy (HS-AFM), is enabling nanometer resolution imaging on millisecond timescales to observe structural-dynamics of single A monomers, oligomers and fibrils. In particular, HS-AFM studies are implementing approaches such as injecting bio-reagents, adjusting salt or monomer concentration and changing temperature on the "fly" during imaging to induce real-time dynamic changes in A, primarily with a focus on fibril growth [9,[19][20][21]. During the time-course of imaging fibrils, some studies have observed the preceding formation of oligomers on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The dimers were less flexible and basically maintained a dumbbell structure in which two spherical structures were connected [110]. Konno and Watanabe-Nakayama et al observed yeast prion Sup35 monomer, oligomer, and fiber elongation [114]. HS-AFM revealed the structural dynamics of the intrinsically disordered (IDR) and partially folded regions of the Sup35 monomer, differences in the core structure and in the IDR between Sup35 oligomers and fibrils, the stepwise growth of oligomers with distinct core size, and the continuous unidirectional elongation of Sup35 fibrils [114].…”
Section: Hs-afm Observation Of Other Amyloidogenic Proteinsmentioning
confidence: 99%
“…α-synuclein fibrils with different structures exhibited different toxicities [7] and caused different AFM was used to capture structural images and measure the nanomechanical properties of individual amyloid aggregates [85][86][87] in the ongoing heterologous aggregation processes of Aβ [20,[88][89][90][91][92][93][94][95][96][97][98], synuclein [90,[99][100][101][102][103][104][105][106], and amylin [107,108]. High-speed AFM (HS-AFM) enabled the kinetic measurement of the structural dynamics of biological molecular processes [79][80][81][82][83][84] including amyloid aggregation [93,[108][109][110][111][112][113][114][115][116]. Here, we show that HS-AFM links structural and dynamics studies, reviewing recent HS-AFM studies and including our findings for Aβ42 [93] and amylin [116], which is associated with ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation